Pengaruh Persepsi Dukungan Guru dan Kecemasan Penggunaan Artificial Intelligence terhadap Motivasi Belajar Siswa Kelas XI di MAN 2 Situbondo - Dina Komariya; Nur Azizah; Dyan Yuliana (METIK Jurnal, 2026)
This study aims to examine the effect of perceived teacher support and Artificial Intelligence (AI) use anxiety on the learning motivation of Grade XI students at MAN 2 Situbondo. A correlational quantitative approach was employed, involving 35 students as respondents selected using total sampling. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination with SPSS version 20. Results indicate that perceived teacher support did not significantly affect learning motivation partially (t=1.288; sig.=0.207>0.05), although all students reported very high levels of perceived support, AI use anxiety did not significantly affect learning motivation partially (t=1.482; sig.=0.148>0.05), with a positive direction suggesting facilitative anxiety, both variables simultaneously did not significantly affect learning motivation (F=2.160; sig.=0.132>0.05), with an R Square of 0.119. These findings indicate that the high homogeneity of perceived teacher support and motivation in a conducive madrasah environment limits statistical detection of their effects. Future research is recommended to expand the population and include variables such as self-efficacy and parental support.